Wide bandgap Cu-Zn-Sn-S compound thin films for transparent semiconductors. Issue 1 (31st December 2022) - Alhazime, Ali A.
Abstract : Transparent semiconductor low cost thin films from benign, earth-abundant materials have been reported. Copper acetate, zinc acetate, stannous chloride, and thiourea have been used as precursors for the preparation of the parent thin film, with dimethyl sulfoxide as the solvent. Both diethanol amine and ethylene glycol have been used as modifiers. Transmittance, reflectance, and absorption coefficient from 190 to 2500 nm for these films have been presented. The linear refractive index n and the absorption index k have been evaluated. Current–voltage curves for the films have been presented. The bandgap for these thin films has been evaluated. From transmittance and the current–voltage measurements, the figure of merit has been calculated. The reported data show that these films are good candidate as electrodes in optoelectronic devices. Highlights Impact of diethanol amine (DEA) and ethylene glycol (EG) as additives for precursors of Cu-Zn-Sn-S nano composite thin films has been reported and characterized These additives change the pH of the precursor solutions and yield changes in optical and electrical properties SEM images show that the films have particle like structure with nanometer scale, and XRD characteristics show that the films are amorphous While DEA decreases the peak reflectance of the pristine film, EG increases it DEA increases the current flow compared to pristine films